Hypotensive, vasorelaxant and antihypertensive activities of the hexane extract of Anacardium occidentale Linn - da Costa, Cintia Danieli F.; Herculano, Edla A.; Silva, Jessyka C.G.; Paulino, Emanuel T.; Bernardino, Alessandro C.; Araújo-Júnior, João X.; Sant’Ana, Antônio Euzébio G.; Salvador, Marcos J.; Ribeiro, Êurica A.N. (Archives of Biological Sciences, 2018)
Paper description: Anacardium occidentale has been widely used in folk medicine in Brazil, India and Africa to treat hypertension. Scientific reports have shown that the extracts of A. occidentale possess cardiovascular actions such as a hypotensive vasorelaxant effects. Our work reports for the first time the effect of the hexane extract from the leaves of this plant using the experimental model of mesenteric artery rings, on blood pressure and heart rate in non-anesthetized normotensive rats, and a antihypertensive effect. Our data suggest that the plant could be used in hypertension management. Abstract: Anacardium occidentale is widely used in folk medicine in Brazil, India, and Africa to treat inflammation, diabetes and hypertension. The aim of the study was to assess the hypotensive, vasorelaxant and antihypertensive effects produced by the hexane extract from the leaves of A. occidentale (HEAO) in rats. The animals were anesthetized, and polyethylene catheters were embedded into the lower abdominal aorta and the inferior vena cava for blood pressure measurements and drug administration. The HEAO was injected and the mean arterial pressure and heart rate were measured. The effects of the HEAO on isolated rat mesenteric rings with and without endothelium were investigated. HEAO induced hypotension and bradycardia in normotensive rats. After pretreatment with L-NAME, indomethacin, atropine or hexamethonium, these effects were attenuated. In mesenteric rings, HEAO antagonized the contractile effects induced by phenylephrine or KCl. This effect was inhibited after removal of the vascular endothelium. Oral administration of the HEAO decreased significant mean arterial pressure in spontaneously hypertensive rats. Mass spectrometric analysis of HEAO identified malic acid and quercetin. Our findings demonstrate that HEAO produces hypotension probably due to a reduction in peripheral vascular resistance, mediated by the endothelium, in part, by a decrease in cardiac output. Bradycardia appears to be due to the indirect activation of cardiac muscarinic receptors via activation of the vagus nerve. The HEAO also induces an antihypertensive effect. https://doi.org/10.2298/ABS171109006C Received: November 9, 2017; Revised: December 29, 2017; Accepted: January 29, 2018; Published online: February 13, 2018 How to cite this article: da Costa CDF, Herculano EA, Silva JCG, Paulino ET, Bernardino AC, Araújo-Júnior JX, Sant’ana AEG, Salvador MJ, Ribeiro ÊAN. Hypotensive, vasorelaxant and antihypertensive activities of the hexane extract of Anacardium occidentale linn. Arch Biol Sci. 208;70(3):…